2007
DOI: 10.1016/j.ijdevneu.2007.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemic condition disturbs the proliferation and cell death of neural progenitors in mouse embryonic spinal cord

Abstract: Spina bifida, which results from failure of fusion in the spinal region of neural tube, is among the most common birth defects associated with diabetic pregnancy. However, the mechanism underlying maternal diabetes-induced congenital malformations including spina bifida is not fully understood. It was hypothesized that hyperglycemic conditions affect the proliferation and apoptosis of neural progenitor cells in the developing spinal neural tube, leading to abnormal neurodevelopment. In the present study, biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 46 publications
3
25
0
Order By: Relevance
“…For example, increased numbers of apoptotic cells have been observed within the fused neural tubes of day 11.5–13.5 mouse embryos [105107]. However, these observations of apoptosis were scattered, and were observed after neural tube fusion, suggesting that they may be involved in further maturation of the CNS, rather than NTD.…”
Section: Altered Gene Expression In Embryos Of Diabetic Mice Leads Tomentioning
confidence: 99%
“…For example, increased numbers of apoptotic cells have been observed within the fused neural tubes of day 11.5–13.5 mouse embryos [105107]. However, these observations of apoptosis were scattered, and were observed after neural tube fusion, suggesting that they may be involved in further maturation of the CNS, rather than NTD.…”
Section: Altered Gene Expression In Embryos Of Diabetic Mice Leads Tomentioning
confidence: 99%
“…Maternal diabetes decreases proliferation and increases apoptosis of neuroepithelial cells in the developing spinal cords of embryos from streptozotocin (STZ)-induced diabetic (type 1) mouse mothers (Gao and Gao 2007). Fetal hyperglycemia exposure may promote neural malformation via oxidative stress (Hockett et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The human brain is particularly vulnerable to the effects of hyperglycemia, and the relative risk of central nervous system malformations is 15.5 times higher than in normal pregnancies (Cannon et al 2002). Previous studies have shown an increased rate of apoptosis and a decreased index of neuronal proliferation during organogenesis associated with disturbed embryonic maturation, increased embryonic resorption and congenital malformations (Gao and Gao 2007;Sun et al 2005;Zhao et al 2009). The results of the present study expand upon these findings by showing that exposure to uncontrolled gestational hyperglycemia can disrupt both neuronal proliferation and neuronal survival in non-malformed embryos from STZ-induced diabetic rats.…”
Section: Discussionmentioning
confidence: 99%